Consideration of human centred emotional design and cultural strategy in urban regeneration in China. Issue 6 (2nd November 2021) - Guo, Fang Bin; Roberts, Emma; Zhan, Xiaochun; Johnston, Kevin
ABSTRACT: Many renovations of former industrial sites in China have failed to respond to the different contexts of location within their design. Resulting from an international funded research project, this paper considers Human-Centred Emotional Design and cultural strategy as urban renovation tools that can attract capital, mark the city as a distinctive brand and encourage interaction and sensual engagement from citizens. This paper pinpoints the project's initial discoveries and captures a range of personal narratives reflecting the real experiences of Chinese people. The findings unlock potential opportunities for culturally coherent regeneration strategies.